Exposure to External Role Models as a Determinant of Entrepreneurial Culture in Southern Nigeria - Brownson, Christabel Divine (Advances in Social Sciences Research Journal, 2017)
Research shows that providing role models could aid in the promotion of positive attitudes towards entrepreneurship. However, while a lot of emphasis has been on parental role models, limited research has focused on the influence of other forms of role models on individuals entrepreneurial decisions with paucity of data on the influence of subjective experience of role models in influencing individuals towards entrepreneurship. Studies have suggested that more than parental influences need to be considered in future research. It is in this regard that this paper investigates the influence of external role models in determining the development of Entrepreneurial Culture in Southern Nigeria. Using a descriptive study, 197 respondents who experienced the use of external role models were examined and findings reveal that the use of external role models other than parental role models does aid in nurturing entrepreneurial culture. The findings contribute new knowledge to the entrepreneurship literature in terms of the use of external role models other than parental role models in stimulating business startups.